Coculture, An Efficient Biotechnology for Mining the Biosynthesis Potential of Macrofungi via Interspecies Interactions - Yu, Guihong; Sun, Yuman; Han, Heyang; Yan, Xiu; Wang, Yu; Ge, Xiaoxuan; Qiao, Bin; Tan, Lingling (Frontiers in Microbiology, 2021)
Macrofungi, which are also known as mushrooms, can produce various bioactive constituents and have become promising resources as lead drugs and foods rich in nutritional value. However, the production of these bioactive constituents under standard laboratory conditions is inefficiency due to the silent expression of their relevant genes. Coculture, as an important activation strategy that simulates the natural living conditions of macrofungi, can activate silent genes or clusters through interspecific interactions. Coculturing not only can trigger the biosynthesis of diverse secondary metabolites and enzymes of macrofungi, but is also useful for uncovering the mechanisms of fungal interspecific interactions and novel gene functions. In this paper, coculturing among macrofungi or between macrofungi and other microorganisms, the triggering and upregulation of secondary metabolites and enzymes, the potential medicinal applications and the fungal-fungal interaction mechanisms are reviewed. Finally, future challenges and perspectives in further advancing coculture systems are discussed.